DOSAGE OF ELECTROPULSE HIGH TONE THERAPY BASED ON RED BLOOD CELLS ELECTROKINETIC PARAMETERS OF CHILDREN WITH CEREBRAL PALSY - E.Yu. Sergeenko; V.V. Polunina ("Paediatrician" Publishers LLC, 2011)
This article contains results of a study dedicated to dosage of electropulse high tone therapy using an express analysis of live cells mobility in alternating current field of children with spastic forms of cerebral palsy. Key words: cerebral palsy, electropulse high tone therapy, dose - effect, cell, electrophoretic mobility of red blood cells, zetapotential. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2011; 10 (6): 204-207)